Case Report: A Novel Truncating Variant of NR0B1 Presented With X-Linked Late-Onset Adrenal Hypoplasia Congenita With Hypogonadotropic Hypogonadism - Zhu, Feng; Zhou, Min; Deng, Xiuling; Li, Yujuan; Xiong, Jing (Frontiers in Endocrinology, 2022)
nuclear receptor subfamily 0 group B member 1 gene (NR0B1) encodes an orphan nuclear receptor that plays a critical role in the development and regulation of the adrenal gland and hypothalamic–pituitary–gonadal axis. In this study, we report a novel mutation in NR0B1 that led to adult-onset adrenal hypoplasia congenita (AHC) and pubertal development failure in a male adult. Clinical examinations revealed hyponatremia, elevated adrenocorticotropic hormone levels, reduced testosterone and gonadotropin levels, and hyper-responses to gonadotropin-releasing hormone and human chorionic gonadotropin stimulation tests. Whole-exome sequencing and Sanger sequencing were performed to identify the potential causes of AHC. Candidate variants were shortlisted based on the X-linked recessive models. Sequence analyses identified a novel hemizygous variant of c.1034delC in exon 1 of NR0B1 at Xp21.2, resulting in a frameshift mutation and premature stop codon formation. The c.1034delC/p.Pro345Argfs*27 in the NR0B1 gene was detected in the hemizygous state in affected males and in the heterozygous state in healthy female family carriers. These results expand the clinical features of AHC as well as the mutation profile of the causative gene NR0B1. Further studies are needed to elucidate the biological effects of the mutation on the development and function of the adrenal gland and the hypothalamic–pituitary–gonadal axis.